Perceived experience of respectful maternity care among mothers attending a selected teaching hospital of Kaski district - Poudel, Sharmila; KC, Deepti; Shrestha, Shreejana (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Pregnancy and childbirth are momentous events in the lives of women and families and represent a time of intense vulnerability. Because parenthood is a uniquely female experience, questions of gender justice and violence are at the heart of maternity care. The study aimed to find out the perceived experience of respectful maternity care and its associated factors among postnatal mothers.Methods: A descriptive cross-sectional research design was used. The study population consisted of mothers who had a normal vaginal delivery and were admitted to the Gandaki Medical College Teaching Hospital and Research Centre’s postnatal ward from July 1 to August 1, 2021. A purposive sampling technique was used. Standard Respectful Maternity Care scale was used to collect the data. Collected data were entered, coded and edited into Statistical package for the social sciences version 16.0 and analyzed using both descriptive and inferential statistical methods.Results: Of total, 166 (83%) women did not receive respectful maternity care. Regarding the dimensions of RMC, more than half 106 (53%) of the mothers received abuse-free care. Only 40 (20%) of the mothers received friendly care. Parity with friendly care adjusted Odds ratio(AOR)=0.25, Confidence interval (CI) (0.10-0.64), education with abuse free care (AOR=3.66, CI 1.86-7.20), Parity with timely care (AOR=3.27, CI=1.45-7.38). Likewise, educational status of the respondent (AOR= 2.24,CI= 1.13-4.44), religion ( AOR=2.88, CI=1.19-6.95) and parity are the factors influencing discrimination free care( AOR= 0.36, CI=0.18-0.73).Conclusions: The majority of women did not receive dignified and respectful care throughout labor.